Layanan Bimbingan Kelompok Problem Based Learning Terhadap Perencanaan Karir Peserta Didik SMA N 1 Kedungwuni - arumsari, nimade; Rakhmawati, Dini; Ajie, G Rohastono (Jurnal Psikoedukasia, 2024)
This article examines career planning for class XI students using problem based learning group guidance services. This type of research is quantitative research. The research method used is true experimental with a research design consisting of an experimental group and a control group. The population of this study was class XI SMA N 1 Kedungwuni, with a total of 324 students. The sample taken was 20 students using purposive sampling technique. The results of this research show that the hypothesis data test was obtained from pre-test and post-test data with a sig value of 0.000 < 0.05, so it can be said that there is a difference in the increase in students' career planning in the group that has been given problem based learning group guidance service treatment. . Based on the results of this research, the suggestion given is that problem based learning group guidance services can be used by guidance and counseling teachers to improve students' career planning. Keywords: Group Guidance, Problem Based Learning, Self-Control